A profile analysis of potential investors in iREIT waqf investment products - Che Embi, Nor Azizan; Ramlee, Roslily; Kassim, Salina (Knowledge E, 2019)
The objective of this study is to provide a profile analysis of potential investors in iREIT as an instrument for waqf asset development. By adopting a survey questionnaire approach, a total of 365 respondents participated in the survey, which assessed information pertaining to the understanding of iREIT as an investment instrument, level of acceptance towards the idea of its introduction in the context of waqf, the medium of promotion and collection that they most prefer, the suitable price, and the unique features that they agreed to have in this hybrid iREIT. The results suggest that majority of the respondents are interested to participate as investors rather than donors, indicating that greater amount of funds can be tapped from the issuance of the iREITs waqf if these preferences of the investors are given priority. Findings of this study would assist in the formulation of an innovative investment structure based on iREIT waqf that is both practical and appealing to the widest pool of investors, and further contribute towards the development of the waqf sector